2020
DOI: 10.1101/2020.11.16.384495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The discriminatory power of the T cell receptor

Abstract: T cells use their T-cell receptors (TCRs) to discriminate between lower-affinity self and higher-affinity non-self pMHC antigens. The strength of this discrimination and the mechanisms that produce it remain controversial. Although a large number of mouse and human TCRs have now been characterised, they have not been used to precisely quantitate discrimination. Here, we systematically quantify the discrimination of TCRs using a discrimination power (α). Early influential studies on three mouse TCRs suggested t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(77 citation statements)
references
References 141 publications
(372 reference statements)
3
73
1
Order By: Relevance
“…The discrepancy between previous work (48, 19, 25, 27) and other human and mouse TCRs (34), including the present work, is likely a result of inaccurate SPR affinity measurements. In addition to temperature and protein aggregation (see Introduction), we have found that extrapolating the K D from non-saturating binding curves reduces precision and underestimates the K D .…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…The discrepancy between previous work (48, 19, 25, 27) and other human and mouse TCRs (34), including the present work, is likely a result of inaccurate SPR affinity measurements. In addition to temperature and protein aggregation (see Introduction), we have found that extrapolating the K D from non-saturating binding curves reduces precision and underestimates the K D .…”
Section: Discussioncontrasting
confidence: 92%
“…The level of antigen discrimination we report in this study and in an analysis of the literature (34) can be explained by the standard KP model. A number of studies, including work from our lab, have reported additional mechanisms beyond the standard KP model to explain the higher level of discrimination originally reported (1732).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations